Transcriptome analysis revealed potential mechanisms of channel catfish growth advantage over blue catfish in a tank culture environment - Wang, Haolong; Su, Baofeng; Zhang, Ying; Shang, Mei; Wang, Jinhai; Johnson, Andrew; Dilawar, Hamza; Bruce, Timothy J.; Dunham, Rex A.; Wang, Xu (Frontiers in Genetics, 2024)
Channel catfish (Ictalurus punctatus) and blue catfish (I. furcatus) are two economically important freshwater aquaculture species in the United States, with channel catfish contributing to nearly half of the country’s aquaculture production. While differences in economic traits have been noted, the extent of transcriptomic variance across various tissues remains largely unexplored. The hybridization of female channel catfish with male blue catfish has led to the development of superior hybrid catfish breeds that exhibit enhanced growth rates and improved disease resistance, which dominate more than half of the total US catfish production. While hybrid catfish have significant growth advantages in earthen ponds, channel catfish were reported to grow faster in tank culture environments. In this study, we confirmed channel fish’s superiority in growth over blue catfish in 60L tanks at 10.8 months of age. In addition, we conducted RNA sequencing experiments and established transcriptomic resources for the heart, liver, intestine, mucus, and muscle of both species. The number of expressed genes varied across tissues, ranging from 5,036 in the muscle to over 20,000 in the mucus. Gene Ontology analysis has revealed the functional specificity of differentially expressed genes (DEGs) within their respective tissues, with significant pathway enrichment in metabolic pathways, immune activity, and stress responses. Noteworthy tissue-specific marker genes, including lrrc10, fabp2, myog, pth1a, hspa9, cyp21a2, agt, and ngtb, have been identified. This transcriptome resource is poised to support future investigations into the molecular mechanisms underlying environment-dependent heterosis and advance genetic breeding efforts of hybrid catfish.